PELATIHAN PEMBELAJARAN BAHASA INGGRIS TERHADAP SISWA DI RUMAH QURAN KHAIRUL UMMAH KECAMATAN GANDAPURA KABUPATEN BIREUEN - Eli Nofriati elinofriati; Chalil As'ari; Iswadi Iswadi; M Afrizal; Misnawati Misnawati (LPPM Universitas Al Muslim, 2021)
The tittle of the community service activity is the training of English Learning toward the students at the Rumah Quran Khairul Ummah Gandapura Subdistrict, Bireuen Regency. The purpose of this training is to solve the problems faced by the students at Rumah Quran Khairul Ummah during the pandemic. In this activity the students were given the training of English learning in order to provide the students with adequate English competence. The training was held for 3 days from 25th until 27th October 2021. The activity was carried out in two sessions; the first session was a presentation of English learning by the team and the second session was the discussing activity where the students are encouraged to ask questions to the teacher and could discuss about the English with their friends. After the training was done, it can be found that the result was the students were motivated and give good responses during the training activity. Through the activity the students also can increase their knowledge about English and can improve their performance in practicing English. Based on the result above, it can be concluded that the training was done successfully.